Girl and the Christmas past - Rivers, A. J. (Coppell, Texas A.J. Rivers, 2022)
"'Twas the night before Christmas, while all of Sherwood were asleep, something sinister and unexpected came out to play... The most wonderful time of the year is here! And at Trinity Pointe Amusement Park all are welcomed. From Santa's Village to the dazzling lights, and the smell of the delicious holiday treats emanating through the air. The merry and festive spirit could be felt at every turn. But all isn't merry as the darkness of the park's past looms over the laughter and joy. The park's unsolved mystery from 6 years ago has left eternal scars for three families. To this day no one could make sense of the senseless violence. Some believe that after such horror the park should never have been reopened. And when a string of park break ins and cryptic messages turn into another nightmare scenario. It seems as though the critics may be right as history is bent on repeating itself, and FBI agent Emma Griffin comes face to face with the horror of Trinity's Holiday Past. Come one and come all for the Christmas surprise you'll never forget!" --
111372
Keywords: United States -- Federal Bureau of Investigation -- Officials and employees -- Fiction; Murder -- Investigation -- Fiction; Missing persons -- Fiction; Women detectives -- Fiction; Employees; Detective and mystery fiction; Fiction; Thrillers (Fiction); Mystery fiction